Liber Amicorum - Steendrukkerij de Jong & Co. 1911-1971. - Bruna, Dick (Hilversum : Steendrukkerij de Jong & Co., 1971)
Aalbers, B.J. ; Aardewerk, Sem ; Agustin, Elisabeth ; Alcopley, Lewin ; Andrea, Kees ; Arendzen, G. ; Arts, Arno ; de Back, Sam ; Badii, Libero ; Banach, Andrzej ; Bantzinger, C.A. ; Barth, Ruoni ; Bayer, Herbert ; Bayl, Friedrich ; Begeer, Jan ; Beltran, Felix ; Benn, Kenneth Day / Ernest ; Benner, Gerrit ; Beran, Gustav ; van den Berg, Jan ; Biesele, Igildo G. ; Bijlsma, Sjoerd ; Blanc, Leo le ; Boas, C. Van emde ; de Boer, C.P.D. ; Bongard, H. ; Bons, J. ; Borgese, Leonardo ; Bos, Ben ; Bouman, B. ; van Boxsel, Pim ; Bramberg, Lars ; Brand, Chris ; Breker, Walter ; van den Broecke, Ko ; Broer, A.L. ; Broer, Henk ; Brozkova, Ivana ; Brun, Donald ; Bruna, A.W. ; Bruna, Dick ; Buitendijk, F.G.J. ; van der Burgt, Flip ; Burkhardt, Klaus ; Burri-Jacobsen, Pia ; Caillois, Roger ; Cairoli, Carlos ; Castro, Lourdes ; Cath, Mr. K.J. ; Centre, Design ; Citroen, Paul ; Clark, Kenneth ; Claus, W.J. ; collins, Martin ; Copier, A.D. ; Costley, Ron ; Crosby, Fletcher, Forbes Ltd. ; Crouwel, Wim ; Cudworth, Jack ; Dance, Jeffrey Jon ; Dark, Just ; David, Jean ; Dean, Michael C.H. ; Dekker, N.A. Douwes ; Dekkers, Ad ; Dekkers, Ger ; Delacroix, Michel ; Doebele, H.P. ; Domela, César ; Dooijes, D. ; Doornekamp, Jopie en henk ; Dresmé, A.J.J. ; Duker, Peter G. ; Dukes, Stacy ; Eckersley, Tom ; Van Eijk, Ria ; Eksell, Olle ; Elburg, Jan G. ; Elenbaas, V. ; Elffers, Dick ; van der Elsken, Ed ; Ernst, Jupp ; eRp, A.E. Massee-van ; Escher, Gielijn ; Evenhuis, Frans ; Florisson, Ton Brouns & Ton ; Fornasetti, Gigi ; Friedlaender, Henri ; Friedman, Yona ; Froshaug, Anthony ; Frutiger, A. ; Garamond, Jacques N. ; Geertzen, Harry ; Glaser, Rene ; de Graaff, Cok ; Gregoire, P. ; Groenendaal, M.H. ; Groot, Jan ; Groot, Pieter ; Haanstra, Joh. ; Haderek, Hans ; Hailstone, Max ; etc.
Nederlands & Engels & Frans & Duits
boek